Fostering University Students’ Attitude toward Utilization of E-Learning - Tarigan, Fatin Nadifa (Journal of Community Research and Service, 2021)
Education is vital in any type of society for the conservation of lives. The existence of education is closely related to the contribution of technology. The growing influences of technologies on all aspects of life require the education sector to follow and adopt technology in its systems. One of them is online learning. This study explores the students’ attitude towards the utilization of e-learning in Universitas Pembinaan Masyarakat Indonesia students especially in Teacher Training and Education Faculty with two study programs namely English Education Study Program and Physical Education, Health and Recreation Study Program. By knowing their attitude then their learning can be fostered by training flipped classroom learning.  The data collection method used was questionnaire distributed to all students of Teacher Training and Education Faculty batch of 2019 by purposive sampling. The findings reveal that technology-related factors (ease of use, speed accessibility and service delivery), internal factors (attitudes of the users) and teacher factors influence the students’attitude toward the use of e-learning. By providing the training, the students increased their motivation and academic performance in online learning. The study could provide the opportunity of assisting the students to use e-learning facilities regularly.